(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
Now the increasing number of the countries gives preference to consideration of the questions connected with ensuring ecological safety. Terminology of ecological safety is considered and also the present situation on various ecological factors in the territory of the Russian Federation is characterized in this article.